Fracture patterns of glass–ionomer cement overlays versus stainless steel bands during endodontic treatment: an ex‐vivo study. (30th March 2013) - Pakdeethai, S.; Abuzar, M.; Parashos, P.
Abstract: Aim: To compare fracture patterns of posterior teeth temporized with: mesio‐occlusal‐distal (MOD) glass–ionomer cement (GIC) interim restorations, stainless steel (SS) bands, GIC dome overlays and GIC dome overlays with occlusal temporary restorations. Methodology: The root canals of 92 extracted human premolars and molars were prepared with rotary NiTi instruments and dressed with calcium hydroxide paste prior to cavity preparation for standardized MOD restorations. Teeth were divided into four groups ( n = 23) and temporarily restored with: GIC interim restorations (GIC group), stainless steel bands (SS group), GIC dome overlays (GIC‐O group) or GIC dome overlays with intermediate restorative material (IRM) in the access cavities (GIC‐IRM group). Teeth were subjected to compressive axial load until fracture; fracture forces and fracture modes were recorded. Statistical analysis included Kaplan–Meier plots, Cox proportional hazards model, one‐way analysis of variance, chi‐square and Fisher's exact tests. Results: There was a significantly higher risk of failure in the GIC group compared with the SS ( P < 0.001), GIC‐O ( P < 0.001) and GIC‐IRM ( P = 0.001) groups. The mean fracture force for SS was significantly higher than GIC‐O ( P = 0.03) and GIC‐IRM ( P < 0.001). GIC fracture force was significantly lower than all other groups ( P < 0.001). Significantly fewer unfavourable fractures were observed in SS compared with GIC ( P = 0.001), GIC‐O ( P = 0.007) and GIC‐IRM ( P < 0.001). Conclusions: Glass–ionomer cement dome overlays with reduced cuspal height and occlusal inclines may be recommended for broken‐down posterior teeth, without any risk of poor aesthetics, gingival irritation or further proximal tooth structure loss. Stainless steel bands may only need to be used in extensively broken‐down teeth or in the presence of parafunctional habits.